2021
DOI: 10.3390/ma14020254
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Concrete Shrinkage Influence on the Performance of Reinforced Concrete Structures

Abstract: The contribution of concrete to the tensile stiffness (tension stiffening) of a reinforced concrete (RC) member is a key governing factor for structural serviceability analyses. However, among the current tension stiffening models, few consider the effect brought forth by concrete shrinkage, and none studies take account of the effect for very long-term shrinkage. The present work intends to tackle this exact issue by testing multiple RC tensile elements (with different bar diameters and reinforcement ratios) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…A proper shrinkage strain measurement is imperative for a proper assessment of the tension stiffening as it may lead to an apparent underestimation [82]. To remove such effect, the authors used some guidelines provided in Fields and Bischoff [83] and found a good agreement with the DOFS experimental results for the rebar 15 M specimens and not so good agreement with the rebar 10 M specimens.…”
Section: Reinforced Concrete Tensile Elements: Steel/concrete Bond Stmentioning
confidence: 99%
“…A proper shrinkage strain measurement is imperative for a proper assessment of the tension stiffening as it may lead to an apparent underestimation [82]. To remove such effect, the authors used some guidelines provided in Fields and Bischoff [83] and found a good agreement with the DOFS experimental results for the rebar 15 M specimens and not so good agreement with the rebar 10 M specimens.…”
Section: Reinforced Concrete Tensile Elements: Steel/concrete Bond Stmentioning
confidence: 99%
“…When concrete is used in building structures, it will be restricted by many factors, such as steel or adjacent structures. Under both the influence of the shrinkage process and external constraints, the concrete matrix usually develops harmful cracking [ 1 , 2 , 3 ]. Due to shrinkage cracking, a pathway is created for the penetration of aggressive agents (i.e., chlorides, sulfate) into the cement-based materials, thereby deteriorating the long-term durability and serviceability of the concrete structure [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drying shrinkage and autogenous shrinkage are the main shrinkage types of cement-based materials. The basic mechanism of shrinkage is that the volume of the microstructure in the cement matrix decreases due to water loss [ 2 , 3 ]. These two kinds of shrinkage occur continuously in the service process of cement-based materials and have a great impact on engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…Material properties have a direct effect on the behavior of structural elements in buildings. It was reported that long-term concrete shrinkage results in a decreased magnitude of the load, causing the occurrence of the first crack in reinforced concrete elements and reducing the tension stiffening mechanism for lower longitudinal reinforcement ratios [8].…”
Section: Introductionmentioning
confidence: 99%